2014
DOI: 10.5144/0256-4947.2014.257
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotic syndrome of minimal change disease following exposure to mercury-containing skin-lightening cream

Abstract: A 28-year-old female suffered from nephrotic syndrome after a long-term use of mercury-containing, skin-lightening cream. The blood and urinary mercury content of this patient increased with use. Renal biopsy showed minimal change disease. Her symptoms were relieved 6 months after discontinuing use of the cream and receiving sodium dimercaptosulfonate and glucocorticosteroid treatments. Proteinuria disappeared, and blood and urinary mercury levels returned to normal. Previous reports of nephrotic syndrome caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…Mercury is absorbed by the skin and can cause many complications such as nephrotic syndrome and peripheral nerve injury. Unfortunately, skinlightening creams containing inorganic mercury are widely used by dark-skinned people to achieve a lighter skin tone [10,18]. In China, TCM can be confused with CFRs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mercury is absorbed by the skin and can cause many complications such as nephrotic syndrome and peripheral nerve injury. Unfortunately, skinlightening creams containing inorganic mercury are widely used by dark-skinned people to achieve a lighter skin tone [10,18]. In China, TCM can be confused with CFRs.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, EMG showed that most nerve damage in patients was caused by CFRs, likely because occupational disease patients tend to be admitted to occupational disease hospitals. Mercury has a strong a nity for renal tissue which can lead to NS [18,[25][26][27]. Mercury-induced MN results from long-term use of mercury-containing skin-lightening cosmetics or from occupational contact with mercury [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“… Total patients with biopsies 97 MN 69 (71.1%) Membranous nephropathy after use of UK-manufactured skin creams containing mercury Chakera et al (2011) [ 18 ] 2 Mercury-induced membranous nephropathy: clinical and pathological features Li et al (2010) [ 6 ] 11 Membranous nephropathy from exposure to mercury in the fluorescent-tube recycling industry Aymaz et al (2001) [ 21 ] 2 Nephrotic syndrome after contact with mercury. A report of five cases, three after the use of ammoniated mercury ointment Becker et al (1962) [ 22 ] 5 MCD 26 (26.8%) Nephrotic syndrome of minimal change diseasefollowing exposure to mercury-containingskin-lightening cream Zhang et al (2014) [ 14 ] 1 Mercury-induced nephrotic syndrome: a case report and review of the literature Wagrowska-Danilewicz et al (2014) [ 23 ] 1 Minimal change disease caused by exposure to mercury-containing skin lightening cream: a report of 4 cases Tang et al (2013) [ 17 ] 4 Minimal-change nephrotic syndrome due to occupational mercury vapor inhalation Campbell et al (2009) [ 24 ] 1 FSGS 2 (2.1%) Mercury-Associated Nephrotic Syndrome: A Case Report and Systematic Review of the Literature Miller et al (2013) [ 25 ] 1 Abbreviations: MN m embranous nephropathy, MCD minimal change disease, FSGS focal segmental glomerular sclerosis …”
Section: Discussionmentioning
confidence: 99%
“…The specific regimen of mercury detoxification was an intramuscular injection (0.125~0.250 g/d) of sodium dimercaptosulfonate (DMPS) for 3 consecutive days followed by a 4-day interval [ 13 , 14 ]. The regimen continued until the urine mercury level dropped to the normal range or severe side-effects occurred.…”
Section: Methodsmentioning
confidence: 99%
“…Significant level of As and Hg was reported with Mohammad et al, 2017 in skin bleaching agents of Caribbean region [50] As used in skin cream and make-up powder causes skin problems, lung cancer, circulatory and peripheral neuropathy, and increased risk of gastrointestinal and urinary tract malignancies [51,52]. Several recent and older studies reported nephrotic syndrome from repeated exposure of mercury and other heavy metals from skin lightening agent [53][54][55][56][57][58]. Dental amalgam has been used as a restorative treatment in dentistry for well over 170 years.…”
Section: Introductionmentioning
confidence: 97%